New palladium catalyzed carbonylation processes for the synthesis of molecules of applicative interest - Ziccarelli, Ida; Mancuso, Raffaella; Gabriele, Bartolo (My University, 2016)
In the present investigation we have developed new palladium-catalyzed carbonylation processes for the synthesis of molecules of applicative interest. In particular, isoindolinone and isobenzofuranimine derivatives have been synthetized starting from 2-alkynylbenzamides by a divergent PdI2-catalyzed multicomponent carbonylative approach, depending on the nature of the external nucleophile and reaction conditions. Thus, oxidative carbonylation of 2- ethynylbenzamides, bearing a terminal triple bond, carried out in the presence of a secondary amine as external nucleophile, selectively led to the formation of 3- [(dialkylcarbamoyl)methylene]isoindolin-1-ones. On the other hand, 3-[(alkoxycarbonyl)methylene]-isobenzofuran-1(3H)imines were selectively obtained when the oxidative carbonylation of 2-alkynylbenzamides, bearing a terminal or an internal triple bond, was carried out in the presence of an alcohol R'OH (such as methanol or ethanol) as the external nucleophile and HC(OR')3 as a dehydrating agent, necessary to avoid substrate hydrolysis. Isoindolinone derivatives were used as starting material to obtain the corresponding spiro-isoindolin isoxazolidines, able to work as inhibitors of the p53-MDM2 interaction: biological test showed that these compounds have antiproliferative activity on cancer cell lines of neuroblastoma, colorectal adenocarcinoma and hepatocarcinoma in the μM range. Isobenzofuranimine derivatives, instead, showed a strong phytotoxic effect on shoot and root systems of Arabidopsis thaliana, a weed which compete with crops for edaphic resources such as water and nutrients. Furo-furanone derivatives have been synthetized by PdI2-catalyzed oxidative carbonylation starting from 4-yn-1,3-diols, substrates bearing themselves nucleophilic groups in a suitable position to give a “double” intramolecular nucleophilic attack so as to obtain functionalized bicyclic molecules. Biological assay showed that these compounds are promising anticancer agents. Finally, part of this PhD was spent at Leibniz Institute for Catalysis in Rostock University in order to develop a new heterogeneous catalyst based on palladium via immobilization and pyrolysis on activated carbon. Palladium supported on N-doped carbon was applied to the alkoxycarbonylation of aryl iodides to benzoates, important feedstocks and key intermediates for pharmaceuticals.
Dottorato Scienza e Tecnica "Bernardino Telesio", indirizzo: Sistemi di Molecole Organiche di Interesse Farmaceutico (OMPI) Ciclo XXVIII, a.a. 2015-2016
Keywords: Carbonylation; Heterocyclic compounds